Menstrual management in transgender and gender diverse individuals: psychiatric and psychosocial considerations - Arshed, Arslaan; Madanes, Sharon; Pottinger, Stephanie; Ackerman, Marra G.; Deutch, Allison B. (Frontiers in Psychiatry, 2024)
The term nonbinary refers to someone whose gender identity does not fall within the culturally and historically normative male/female gender paradigm. Some individuals may identify as masculine, two-spirit, or masculine of center (MoC), indicating that although they may not identify as female or male, their identity and feelings present more masculine than feminine. Some indigenous individuals may also identify as two-spirit, a third "suprabinary" gender that has been adopted for over 30 years (2). To achieve inclusivity for this article, we use the term transgender and genderdiverse (TGD) to denote the diversity of transgender, nonbinary, and MoC identities, and menstruators to describe individuals who menstruate. To achieve inclusivity with gender identity and the spectrum of masculinity, femininity, and nonbinary individuals who menstruate, we use the term menstruator. Additionally, we use the term TGD-AFAB and TGD-menstruator interchangeably. A glossary of terms and gender-inclusive language in Table 1.